1986
DOI: 10.1038/icb.1986.60
|View full text |Cite
|
Sign up to set email alerts
|

Haemagglutination Patterns of Aeromonas Spp. Related to Species and Source of Strains

Abstract: The study included 138 A. sobria and 182^1. hydrophila isolated in Perth from samples of diarrhoeal or non-diarrhoeal faeces or from domestic water. Strains were grouped in relation to agglutination of human, horse, rat and guinea pig erythrocytes and the effect of sugars on haemagglutination. Agglutination of red cells of all four species (primary group 1) was most commonly associated with A. sobria, particularly those strains isolated from faeces of patients with diarrhoea. Most A. hydrophila associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 15 publications
6
19
0
Order By: Relevance
“…There is evidence that haemagglutination patterns vary under different test conditions [2,4], so that putatively different haemagglutination types may merely reflect different amounts of the same haemagglutinin produced under different in vitro conditions. Geographic variation in haemagglutination inhibition patterns has also been noted (17). In the present study nonagglutinating isolates were more likely to be A. caviae than A. hydrophila or A. sobria and this confirms previous findings [17,37].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…There is evidence that haemagglutination patterns vary under different test conditions [2,4], so that putatively different haemagglutination types may merely reflect different amounts of the same haemagglutinin produced under different in vitro conditions. Geographic variation in haemagglutination inhibition patterns has also been noted (17). In the present study nonagglutinating isolates were more likely to be A. caviae than A. hydrophila or A. sobria and this confirms previous findings [17,37].…”
Section: Discussionsupporting
confidence: 91%
“…Geographic variation in haemagglutination inhibition patterns has also been noted (17). In the present study nonagglutinating isolates were more likely to be A. caviae than A. hydrophila or A. sobria and this confirms previous findings [17,37]. Significant differences in the distribution of haemagglutinin types between the three species of aeromonads have been shown by some workers, the F-G-M' pattern for example being typical of A. sobria [49].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, only 39 YO of Aeromonas strains in group F + G + M + were cytotoxin producers. In contrast, Burke et al, 15 as well as Singh and S a n~a l ,~~ reported a higher degree of association between enterotoxin production by Aeromonas strains and inhibition of HA in the same group (F + G + M +). The interpretation of other inhibition patterns is not conclusive.…”
Section: -35mentioning
confidence: 73%
“…Results show a strong association (100 YO) between cytotoxin production by Aeromonas strains and HA1 in groups F -G -M + and F -G + M + . Burke et al 15 reported that 75% of Aeromonas strains in these groups were enterotoxigenic, whereas Singh and S a n~a l~~ found that most of their strains in group F -G + M + were non-toxigenic. In the present study, only 39 YO of Aeromonas strains in group F + G + M + were cytotoxin producers.…”
Section: -35mentioning
confidence: 99%